Who Pays for Unions? - Dodini, Samuel; Stansbury, Anna; Willén, Alexander (Quarterly Journal of Economics, 2026)
Abstract If unions raise worker wages, who pays? We provide a comprehensive assessment of firm responses to increased unionization, using changes in the tax deductibility of union dues in Norway as a quasi-exogenous source of variation in firm-level union density. In the average private sector firm, higher union density raises labor costs and leads firms to contract employment and production, lowering profits without increasing the labor share. The incidence is shared: consumers bear part of the cost through higher prices, shareholders through lower profits, and the remainder is offset by productivity improvements. The total wage bill falls, with losses concentrated among less-attached “outsider” workers. Firm responses vary systematically by the degree of market competition. In manufacturing, where firms operate in less competitive product and labor markets, the response is reversed: the average firm expands employment and production, reduces labor markdowns, and does not experience profit declines. Instead, higher labor costs are largely passed on to consumers through higher prices, with the remainder offset by productivity gains. Workers benefit as both wages and employment rise. These patterns suggest that unions can offset employer monopsony power and that firm responses–and therefore who ultimately bears the cost-depend importantly on market structure. Overall, unionization in this setting primarily redistributes from consumers rather than shareholders and has effects that differ sharply across firms, including a reallocation toward larger and more productive firms. We rationalize these patterns using a partial-equilibrium model of union bargaining with product- and labor-market power.